Capacity strengthening for agricultural policy analysis and research in Nigeria: A roadmap towards a strategy - Sanyal, Prabuddha; Babu, Suresh Chandra (International Food Policy Research Institute, 2010)
This paper deals with the human resource development and institutional capacity strengthening in Nigeria as they relate to policy analysis and research capacity in addressing the problems of poverty and food security. The findings of the paper show that there exist several human, physical, and institutional capacity gaps for designing and implementing agricultural policies in Nigeria.